Identifikasi IDENTIFIKASI TELUR NEMATODA USUS SOIL TRANSMITTED HELMINTH PADA FESES DAN KOTORAN KUKU PETANI SAWAH DI DESA MUNGGUR KECAMATAN MANYARAN WONOGIRI - Tr Mulyo Wati (LPPM Universitas Abdurrab, 2021)
Soil Transmitted Helminth (STH) is an intestinal nematode that causes helminth infections that are transmitted through soil to develop into an infective form. Species belonging to the intestinal nematodes of the STH group are Ascaris lumbricoides, Trichuris trichiura, Ancylostoma duodenale, Necator americanus and Strongyloides stercoralis. Humans can be infected by accidentally ingesting worm eggs or through skin penetration due to direct contact with soil without personal protective equipment. The purpose of this study was to determine the percentage of rice farmers in Munggur Village, Manyaran Wonogiri District who were infected with the intestinal nematode STH.. This research method uses an observational method with a cross sectional approach. Examination of the stool samples used the direct method with 0,9% NaCl solution and 1-2% Lugol solution, while the nail samples used the sedimentation method with 0,25% NaOH solution plus 1-2% Lugol solution. The results of the examination on the stool samples found the presence of STH intestinal nematode eggs, while in the nail feces no STH intestinal nematode eggs were found. The conclusion of this study was the presence of STH intestinal nematode eggs in stool sample number 12.13 with the discovery of Hookworm eggs. The percentage of examination results on stool samples was declared positive at 10% and negative stool samples were stated negative at 90%, while nail dirt samples were declared positive at 0% and negative samples were stated at 100%. Keywords: Soil Transmitted Helminth, feces, nail dirt